Observation of Serum Ascites Albumin Gradient Values among Children with Ascites (The Planet, 2024)
Introduction: The serum ascites albumin gradient (SAAG) represents the difference in concentration between serum albumin and ascitic fluid albumin. Various studies have consistently shown a direct correlation between SAAG and portal pressure. A high SAAG value is indicative of portal hypertension. Aim of the study: This study aimed to observe the serum ascites albumin gradient values among children with ascites. Methods and Materials: This cross-sectional study was conducted in the Dhaka Medical College Hospital (DMCH) and Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from Jan 2009 to July 2009. A total of 40 consecutive patients with ascites were selected as study subjects using a purposive sampling technique. The data were analyzed using SPSS version 23.0. Results: In this study, 85% of nephrotic syndrome cases had a serum ascites albumin gradient (SAAG) < 1.1 gm/dl, while 15% had SAAG ≥1.1 gm/dl. For chronic liver disease, SAAG was ≥1.1 gm/dl in 92.85% and < 1.1 gm/dl in 7.15%. SAAG was consistently < 1.1 gm/dl in disseminated tuberculosis and protein-losing enteropathy but ≥1.1 gm/dl in congestive cardiac failure. Mean SAAG values in nephrotic syndrome, chronic liver disease, disseminated tuberculosis, protein-losing enteropathy, and congestive cardiac failure were 0.72±0.37, 1.63±0.49, 0.68±0.25, 1±0, and 2.30±0, respectively, with highly significant differences (P
Keywords: Serum ascites albumin gradient; SAAG; Ascitic fluid albumin; Nephrotic syndrome; Chronic liver disease; Children